2014
DOI: 10.1088/1674-1056/23/1/018104
|View full text |Cite
|
Sign up to set email alerts
|

The basis of organic spintronics: Fabrication of organic spin valves

Abstract: Organic spintronics focuses on utilizing the spin degree of freedom in organic materials because of the long spin relaxation time. The vertical organic spin valve (OSV) is a typical sample structure used to study the spin transport phenomena. However, the fabrication of high quality OSVs is difficult, which results in controversial experiment results and hence hinders the development of organic spintronics. In this work, we describe our recent study on the fabrication of typical vertical organic spin valves, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In order to minimize the metal inclusion into the organic layers and hence to avoid the short circuit and to improve the accuracy of the thickness characterization, a few advances have been made recently in depositing the top FM electrodes. Chen et al showed the deposition of an FM electrode using back scattering method to avoid the direct hit of the metallic atoms onto the organic films . This method was reported to enhance the MR and was shown promising for the reproducibility of the OSV performance although unintentional impurities might be introduced during the slow metal evaporation due to quite low chamber vacuum (10 –3 torr).…”
Section: Advances In Organic Spin Valvesmentioning
confidence: 99%
“…In order to minimize the metal inclusion into the organic layers and hence to avoid the short circuit and to improve the accuracy of the thickness characterization, a few advances have been made recently in depositing the top FM electrodes. Chen et al showed the deposition of an FM electrode using back scattering method to avoid the direct hit of the metallic atoms onto the organic films . This method was reported to enhance the MR and was shown promising for the reproducibility of the OSV performance although unintentional impurities might be introduced during the slow metal evaporation due to quite low chamber vacuum (10 –3 torr).…”
Section: Advances In Organic Spin Valvesmentioning
confidence: 99%
“…As a spin injection source, atomic flat LSMO electrode was grown on SrTiO 3 (001) by a DC facing-target magnetron sputtering method. AlO x was used as a buffer layer to protect against Co penetration and doping into P3HT spacer, reducing the thickness of ill-defined layer . Also, it could adjust the energy band alignment at the interface to facilitate the spin polarized carrier injection .…”
Section: Introductionmentioning
confidence: 99%
“…AlO x was used as a buffer layer to protect against Co penetration and doping into P3HT spacer, reducing the thickness of ill-defined layer. 27 Also, it could adjust the energy band alignment at the interface to facilitate the spin polarized carrier injection. 28 Along with a spin detection analyzer of 10 nm Co evaporated on top, up to 15.6% low-temperature magnetoresistance was achieved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21,22 For this purpose, based on first-principles studies, we explored the properties of the BC 7 sheets induced by different biaxial strain. 21,22 For this purpose, based on first-principles studies, we explored the properties of the BC 7 sheets induced by different biaxial strain.…”
Section: Discussionmentioning
confidence: 99%